An analysis of the etiologies and economic indexes of inpatients with stage 5 chronic kidney disease in North China - Guo, Shan-Shan; Gou, Yan-Li; Li, Jian-Dong; Zhang, Hong-Fang; Huang, Yang; Zheng, Xi-Jie; Chen, Hang; Sui, Zhun (Frontiers in Public Health, 2022)
Objective The aim of this study was to analyse the epidemiological characteristics of the causes of chronic kidney disease (CKD) stage 5 patients in North China and to investigate the economic burden of those on haemodialysis (HD) or peritoneal dialysis (PD), as well as the associated influencing factors. Methods General clinical information, etiological categories, and hospitalization costs for HD or PD were collected from 1,515 patients hospitalized with stage 5 CKD at the Affiliated Hospital of Hebei University from 2016 to 2018. Logistic regression analysis was used to analyze the independent influencing factors affecting patients' financial burden. Results: The highest rate of DN was found in patients aged 70 years or older (27.0%) and the highest incidence of primary glomerulopathy was found in patients aged less than 50 years (24.3%). Age, type of dialysis, and type of health insurance were independent influences on the total financial burden of patients, and the results of multifactorial logistic regression analysis showed that age [OR (95% CI): 1.009 ( 1.002,1.020)] and type of dialysis [OR (95% CI): 1.746 (1.149,2.659)] would increase the total financial burden. The type of health insurance would reduce the total financial burden [OR (95% CI): 0.222 (0.108,0.418)]. Conclusion: Chronic kidney disease, with its complex etiology and the heavy financial burden required for treatment, remains a more serious public health problem globally, and it is therefore necessary to further improve medical coverage for dialysis patients, increase management efforts, broaden pro-poor policies and increase the accessibility of medical services in low- and middle-income areas.